Report on coal boring operations at the head of the Grand Lake [electronic resource] - Howley, James P., 1847-1918.; Newfoundland. Geological Survey. (St. John's, Nfld. : Robinson, 1917)
Running title: Geological Survey of Newfoundland report for 1893. "For the year 1893." Electronic reproduction. Mode of access: Internet. 44